The White Coat Diaries - Sinha, Madi (New York : Berkley, 2020)
"Grey's Anatomy meets Scrubs in this brilliant debut novel about a young doctor's struggle to survive residency, love, and life. Having spent the last twenty-something years with her nose in a textbook, brilliant and driven Norah Kapadia has just landed the medical residency of her dreams. But after a disastrous first day, she's ready to quit. Disgruntled patients, sleep deprivation, and her duty to be the "perfect Indian daughter" have her questioning her future as a doctor. Enter chief resident Ethan Cantor. He's everything Norah aspires to be: respected by the attendings, calm during emergencies, and charismatic with the patients. As he morphs from Norah's mentor to something more, it seems her luck is finally changing. When a fatal medical mistake is made, pulling Norah into a cover-up, she must decide how far she's willing to go to protect the secret. What if "doing no harm" means risking her career and the future for which she's worked so hard?"-- Provided by publisher.
Keywords: Love stories